Antibacterial effects of mineral trioxide aggregate and Biodentine TM after the addition of different concentrations of black seed aqueous solutions - Shalan, Linz A; Al-Hashimi, Majida K (Journal of Baghdad College of Dentistry, 2015)
Background: Mineral Trioxide Aggregate (MTA) and BiodentineTM cements are new materials with numerous exciting clinical applications. Both have appreciable properties which include good physical properties and the ability to stimulate tissue regeneration as well as good antibacterial effects. The aim of this study was to investigate and compare the antibacterial effects of MTA and BiodentineTM, when they were mixed with different concentrations of aqueous solutions of Black Seed extract, against Enterococcus faecalis.Materials and methods: MTA and BiodentineTMwere prepared according to the manufacturerâ€™s instructions. The method of Mawlood was followed to prepare the Black Seed aqueous solution. Agar diffusion method on Brain Heart Infusion agar was employed.Twenty, 9 cm diameter, petri-plates with 25 ml of Muller Hinton agar media were prepared. A sterile spreader was used to inoculate the microorganisms. With a micropipette 0.1 ml of the Enterococcus faecalis suspension was added to the surface of the plates. Within 15 minutes, after inoculation of the plates, 4 cavities, each one measuring 5 mm in diameter and 4 mm in depth, were made in each agar plate. A total of 20 agar plates were divided into 2 groups consisted of 10 plates each; Group A: each plate contained 4 wells filled with MTA alone and MTA mixed with 10%, 30% and 50% of Black Seed aqueous solutions respectively.Group B: each plate contained 4 wells filled with BiodentineTMalone and BiodentineTMmixed with 10%, 30% and 50% of Black Seed aqueous solutionsrespectively. Next day after incubation, the agar plates were examined for bacterial inhibition zones. With a scientific ruler the diameter of the antibacterial inhibition zones were measured. The data were recorded and statistically analyzed, by the ANOVA and the Student's t-test.Results: Both cements had antibacterial effects, which were increased with the addition of the aqueous solutions of Black Seed extract. The increase in the diameter of Enterococcus faecalis inhibition zones was directly proportional with the increase in the concentration of the added Black Seed aqueous extract. Conclusion: Adding aqueous solutions of Black Seed extract to both MTA and Biodentineâ„¢ increased their potential to inhibit the growth of Enterococcus faecalis. Key words: Mineral Trioxide Aggregate, Biodentine TM, Black Seed.